Ecranisation Of Plot From Novel To Film Of Maze Runner: The Death Cure - Neha, Dinda Cahya; Endang Woro Kasih, E Ngestirosa (Berumpun: International Journal of Social, Politics, and Humanities, 2024)
This research focuses on the form of ecranisation the storyline adaptation from the novel to the film Maze Runner: The Death Cure. The purpose of this research is to describe the forms of ecranisation (addition, alteration, and compression) through a comparison of the narrative facts from the novel to the film. This study employs a literature study approach with a qualitative descriptive method. The data consists of words, phrases, and sentences found in the novel and the film script. The data collection techniques in this study include reading, noting, observing, transcribing the film into a script, translating the film script, and classifying the data. The analysis techniques used are data reduction, data presentation, and drawing conclusions. This research will utilize comparative literature theory, narrative facts (plot, characters, and setting), and ecranisation (addition, alteration, and compression). The results of this research show that the comparison between the novel Maze Runner: The Death Cure and the film has narrative similarities and employs a mixed plot structure. The differences observed are evident in the introduction of new plots and settings in the film. This occurs due to the condensation of the story in the film; not all information from the novel can be fully incorporated into the film. The form of ecranisation (changes) that occurs in adapting the novel Maze Runner: The Death Cure into the film tends to include more additions, such as the introduction of new settings and plots. This happens because the past setting is not prominently featured, and there are elements of adult themes within it, indicating that every process of ecranisation inevitably experiences changes.